COVID-19-Related Stressors and Chinese Adolescents' Adjustment: The Moderating Role of Coping and Online Learning Satisfaction - Li, Xiaoshan; Tang, Xiujuan; Wu, Hou; Sun, Pengyong; Wang, Min; Li, Li (Frontiers in Psychiatry, 2021)
Present study aimed to examine the main and interactive relations of COVID-19-related stressors, coping and online learning satisfaction with Chinese adolescents’ adjustment during the COVID-19 pandemic. A total of 850 adolescents from three Chinese secondary schools participated in survey during the pandemic outbreak, and the data was analyzed by the hierarchy linear regression approach. Results showed that COVID-19-related stressor was a vulnerable factor in predicting adjustment. Both individual-level (e.g., coping) or class-level characteristics (e.g., class-level indicator of coping) could attribute to adolescents’ adjustment. Specifically, problem-based coping and online learning satisfaction can promote adolescents’ adjustment directly or served as a buffer against the negative impact of stressors on adjustment, while emotion-based coping was a vulnerable factor in predicting adjustment directly or served as a risk factor in strengthening the relation of stressors and adjustment. Comparing with male adolescents or those adolescents with high socioeconomic status, female or impoverished adolescents reported poorer adjustment during the COVID-19 pandemic. These findings enrich our understanding about the impact of the COVID-19 pandemic on adolescents’ adjustment, and are helpful in improving adolescents’ adjustment during the pandemic.